The Impact of Financial Inclusion, Fintech Adoption, and Frugal Living on the Financial Behavior of GenBI Students - Rifda Finastri; Susanti (Journal of Educational Management Research, 2026)
This study aims to examine the influence of financial inclusion, financial technology (fintech) usage, and frugal living on the financial behavior of GenBI students, particularly in shaping saving behavior. A quantitative causal research design was applied using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The sample consisted of 242 respondents selected through probability sampling, and data were collected using structured questionnaires with a five-point Likert scale. The results show that financial inclusion, fintech usage, and frugal living each have a positive and significant effect on financial behavior. In addition, all variables collectively have a significant influence on students’ saving behavior. Among the three predictors, financial inclusion emerges as the most dominant factor, followed by fintech usage and frugal living. These findings confirm that financial behavior is shaped by a combination of access to financial services, digital financial literacy, and lifestyle discipline rather than a single determinant. The implications of this study suggest that strengthening financial education, expanding digital financial literacy, and encouraging responsible consumption behavior are essential to improving students’ financial management.